Feasibility and performance of continuous glucose monitoring in hyperglycemia after lung transplantation - Munoz Pena, Juan M.; Algarra, Kimberly; Kennedy, Hannah; Leong, Man Chong; Salloum, Ramzi G. (Frontiers in Transplantation, 2024)
Background: Post-Transplant Diabetes Mellitus (PTDM) affects 20-40% of lung transplant recipients within five years, impacting rejection, infection, cardiovascular events, and mortality. Continuous glucose monitoring (CGM) is used in diabetes but not well-studied in PTDM.Objective: This study assessed CGM performance in detecting hypoglycemia and hyperglycemia post-lung transplantation, compared to self-monitoring blood glucose.A prospective pilot study included 15 lung transplant patients (mean age 58.6 years; 53.3% men; 73.3% with pre-transplantation diabetes) managing hyperglycemia with insulin. Patients used a blinded CGM and self-monitored glucose for ten days. Data were categorized (% time in range, % high, % very high, % low, % very low) and compared using paired t-tests.Results: CGM showed superior hyperglycemia detection. Mean differences for "% very high," "% high," and "% high and % very high" were 7.12 (95% CI, 1.8-12.4), 11.1 (95% CI, 3.5-18.8), and 18.3 (95% CI: 7.37-29.24), respectively. No significant difference was found for "% low and % very low." All patients reported a positive CGM experience.CGM use post-lung transplantation seems feasible and offers advantages in detecting hyperglycemia and in optimizing glucose management. Study limitations include a small sample size, requiring larger studies to assess glycemic control, hypoglycemia detection, and transplant outcomes.